The Revised Treaty of Chaguaramas : the dispute settlement of the CSME may well be its undoing : the recourse to arbitration revisited - Waite, Prince Neto D. C. B. (2008)
Outlines why legal certainty is critical to a successful functioning of the CSME. Illustrates the suggested modus operandi of the arbitral tribunal in order to create an environment with legal certainty.